Fictile tubules: A traditional Mediterranean construction technique for masonry vaulted systems. (30th December 2018) - Scuro, Carmelo; Tiberti, Simone; Codispoti, Rosamaria; Milani, Gabriele; Olivito, Renato S.
Highlights: Fictile tubules are hollow, cylindrical clay bricks (tubules, amphorae, caroselli ). Employed in many heritage buildings in and around Mediterranean area. Caroselli 's compressive strength influenced by number of microorganisms' imprints. Derivation of homogenised properties for composite material caroselli + mortar. Satisfying fitting of homogenised properties against experimental data. Abstract: The historical centres of many Italian cities are integral parts of the Country's cultural heritage, and guaranteeing their conservation over time is paramount. Many constructions are characterised by building techniques that are not well-known and still have to be studied. In particular, one technique involving the use of clay fictile tubules is here examined through historical studies, experimental characterisation and numerical investigations. This technique is typical of the Mediterranean area and Southern Italy, and dates back to Roman and early Christian times; three different types of elements were usually employed (tubules, amphorae and caroselli ). Walls, domes and vaulted structures with different geometries were built with this technique, which allowed for the creation of modular construction elements in potteries. Relevant historical building issues are first addressed in detail, then a comprehensive experimental investigation on the constitutive materials ( caroselli and mortar) is presented, provided with a series of numerical simulations aimed at validating the experimental results. Eventually, the composite material consisting of caroselli and mortar is investigated through a homogenisation approach, allowing its mechanical characterisation through the evaluation of equivalent homogenised material properties. They are derived through the investigation of an analytical elementary cell, subject to uniaxial tension and compression, which enables to derive homogenised constitutive laws. These are validated by comparing experimental data obtained from compressive tests performed on three real elementary cells with numerical results gathered from the use of such homogenised properties on an equivalent cell.